Silica Supported Perchloric acid (HClO4-SiO2) Catalyzed Synthesis of 8,10-Dimethyl- 8,12-dihydro-12-aryl-9H-naphtho- [1’,2’:5,6]pyrano[2,3-d]pyrimidine-9,11(10H)-diones Under Solvent-Free Conditions - Wu, Liqiang; Wang, Xiao; Yang, Limin; Yan, Fulin (Asian Journal of Chemistry, 2010)
The reaction of b-naphthol with arylaldehydes and 1,3-dimethylbarbituric acid in the presence of HClO4-SiO2 (3 mol %) under solvent-free conditions led to 8,10-dimethyl-8,12-dihydro-12-aryl-9H-naphtho-[1',2':5,6]pyrano[2,3-d]pyrimidine-9,11(10H)-diones in good yield.